2009
DOI: 10.1097/bot.0b013e31818f8dc1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Morphology of the Posteromedial Fragment in Bicondylar Tibial Plateau Fractures

Abstract: Given the high frequency, significant portion of the joint involved, significant displacement, and pattern suggestive of instability, surgeons need to be cognizant of this pattern and may need to consider directly reducing and fixating this fragment through a posteromedially based approach. Overall morphologic findings of the posteromedial fragment are highly consistent with other recent data on this pattern. This information may also be useful in modeling fracture fixation for future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
109
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(120 citation statements)
references
References 28 publications
3
109
0
8
Order By: Relevance
“…We note that the morphological characteristics of the complex bicondylar four-quadrant tibial plateau fractures follow a regular pattern, which was also described by others [8][9][10][11][12]. The concave medial plateau is usually split into two large fragments (posteromedial and anteromedial) without articular depression, while the convex lateral plateau is split-depressed into various degrees of multi-fragments with broadening of the lateral compartment (anterolateral and posterolateral).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…We note that the morphological characteristics of the complex bicondylar four-quadrant tibial plateau fractures follow a regular pattern, which was also described by others [8][9][10][11][12]. The concave medial plateau is usually split into two large fragments (posteromedial and anteromedial) without articular depression, while the convex lateral plateau is split-depressed into various degrees of multi-fragments with broadening of the lateral compartment (anterolateral and posterolateral).…”
Section: Discussionmentioning
confidence: 63%
“…Chang et al [6,7] classified the tibial articular plateau into four-quadrants, and the fractures are categorized with an isolated single quadrant (anteromedial, anterolateral, posteromedial, and posterolateral) and different combinations of 2, 3 and 4 quadrants. The fracture on each quadrant may have unique characteristics [8][9][10][11][12] as well as require related incision or treatment protocols [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Barei et al [2] and Higgins et al [24] reported that the incidence rate of posteromedial fragments in patients with Bicondylar tibial plateau fractures was 28.8-59%. The presentation of posteromedial fragments makes reduction and fixation of complex plateau fractures more difficult, especially when a single fixed angle plate is used.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Evaluation of these fractures with computed tomography and three dimensional (3-D) reconstructions has shown presence of posteromedial fragment in most of these cases. 4 If not treated timely and adequately these fractures can lead to late onset disabilities. With recent change in trends, most of the authors recommend open reduction and internal fixation (ORIF) for these fractures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Several biomechanical studies have proved that fixation of these fragment is necessary to prevent secondary loss of alignment like varus collapse. 4 We have tried to assess the outcome of these fractures using ORIF with locking or buttress plate through Lobenhoffer approach.…”
Section: Introductionmentioning
confidence: 99%